Modern views on the problem of antifungal resistance of strains of fungi of the genera Fusarium and Aspergillus in the context of the concept of One Health - Hrynzovska, Anastasiia; Bobyr , Vitalii (The Ukrainian Scientific Medical Youth Journal, 2023)
the «One Health» concept integrates human, animal and environmental health and emphasizes the need for collaboration between different sectors such as medicine, veterinary medicine, ecology, public health and other sciences to achieve greater understanding and management of common health threats. This concept arose from the realization that many diseases, including infectious diseases, cancer and mental disorders, have common roots related to the state of the ecosystem. For example, the spread of infectious diseases can be caused by climate changes, loss of biodiversity, inappropriate use of antibiotics, xenobiotics, and other factors. In addition, pathogens of animal diseases can also acquire pathogenic properties and pose a threat to public health. «One Health» implements such an approach to health, which instead of the traditional vertical approach is system-oriented, it encourages comprehensive actions to prevent and control disease at different levels. This approach includes comprehensive medical diagnostics, monitoring, research and coordination, as well as strengthening cooperation between scientists, doctors, veterinarians, ecologists and other specialists. Undoubtedly, an important issue in the context of the implementation of the «One Health» concept is the study of the formation of resistance to antifungal drugs in microscopic fungi, including representatives of the genera Fusarium and Aspergillus. The ratio of natural to artificial resistance can be highly variable among different fungal strains, even within the same species or genus. This is due to the genetic diversity of fungi and their ability to mutate and adapt to new conditions. Considering these factors, it is important to constantly monitor the resistance of mycelial fungi to antifungal drugs and detect the emergence of new resistant strains. This will make it possible to use antimicrobials correctly and provide effective treatment.